Dinamika Hubungan Antara Pengujian Undang-Undang dengan Pembentukan Undang-Undang - Utomo, Nurrahman Aji (Jurnal Konstitusi, 2015)
The development and implementation of a relationship leading to the birth of anomalous friction decision Judicial review to collide against the lawmaking function. The absence of a follow-up mechanism to cancel the decision of the norm, led to the birth anomaly judgment. Friction Judicial Review with Law making Function was born in the form of vague and superficial to the lack of follow-up mechanisms. Efforts to reduce the friction between the two of them was done to achieve the ideal relationship between judicial review with lawmaking function.